2011
DOI: 10.1590/s1517-86922011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do número e intensidade das ações excêntricas nos indicadores de dano muscular

Abstract: A single bout of resistance training, especially those comprising the performance of eccentric actions, induces damage to the muscle structure. Some characteristics of the eccentric exercise bout (i.e. the number and the intensity of contractions) may increase muscle damage. Thus, the aim of this study was to investigate if the number and the intensity of the eccentric muscle actions significantly increase muscle damage (as evaluated through alterations in indirect markers of muscle damage). Twenty-four young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…This relationship between experience and number of injuries has been described very often. (Lystad et al 2015, Buse 2006, Barroso et al 2011, Ramos et al 2015 Confirming our study, some authors have shown a high rate of injuries (70-82%) during practicing sessions. (Buse 2006, Loosemore et al 2006 Barsottini et al ( 2006) described an incidence of 71% of orthopedic injuries during practicing.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This relationship between experience and number of injuries has been described very often. (Lystad et al 2015, Buse 2006, Barroso et al 2011, Ramos et al 2015 Confirming our study, some authors have shown a high rate of injuries (70-82%) during practicing sessions. (Buse 2006, Loosemore et al 2006 Barsottini et al ( 2006) described an incidence of 71% of orthopedic injuries during practicing.…”
Section: Resultssupporting
confidence: 87%
“…EP presented a higher FI when compared to other protocols, these data confirm previous findings that report a drop in mechanical performance of muscle actions (Eches, Ribeiro, Nascimento, & Cyrino, 2013). This decrease in the number of repetitions especially in EP, seems to be due to a functional impairment of muscle that is related to an increased enzyme activity of DOMS markers such as CK and LDH, besides a smaller range of motion (Paulsen, Mikkelsen, Raastad, & Peake, 2012;Philippou et al, 2012), and may be related more to exercise intensity than properly the CE (Barroso, Roschel, Gil, Ugrinowitsch, & Tricoli, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The same consensus explains that this increase and recovery are proportional to the physical exercise intensity. Once again, the idea that the time and the number of muscle contractions promoted a higher intensity to the exercise than the percentage of 1RM is reinforced (3,12) because it was significant in the BFR and LI groups, but not in the HI one.…”
Section: Discussionmentioning
confidence: 99%
“…Tais alterações provocam aumento nos valores dos marcadores de agressão tecidual na corrente sanguínea e nas propriedades mecânicas, tais como: concentração de CK, sensação de dor e amplitude do movimento 1,11 . Neste sentido, observa-se que as técnicas crioterápicas mais acessíveis para população de maneira geral, para prevenir e tratar as alterações no músculo após o exercício, são as bolsas térmicas e a massagem direta com o gelo, por serem de fácil acesso e baixo custo 4,12 .…”
Section: Discussionunclassified